2009
DOI: 10.1152/physiolgenomics.90245.2008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of a major mouse obesity QTL (Carfhg2): integration of gene expression and causality modeling

Abstract: HG.CAST-(D9Mit249-D9Mit133) (HG9) congenic mice are homozygous for CAST/EiJ chromosome (Chr) 9 alleles from approximately 9 to 84 Mbp on a C57BL6/J-hg/hg (HG) background. This region contains the carcass fat in high growth mice (Carfhg2) quantitative trait locus (QTL), and while its obesity-promoting effects have been confirmed in HG9 mice, its underlying genetic basis remains elusive. To refine the location of Carfhg2, we preformed a linkage analysis in two congenic F2 intercrosses and progeny-tested a recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…One limitation of this approach is that it will not be successful in cases in which the responsible variant(s) does not affect expression or in which the change in expression is specific to a tissue not investigated. Despite this limitation, our work and that of others illustrates the power of eQTL analysis for gene discovery (25,47,48).…”
Section: Discussionmentioning
confidence: 81%
“…One limitation of this approach is that it will not be successful in cases in which the responsible variant(s) does not affect expression or in which the change in expression is specific to a tissue not investigated. Despite this limitation, our work and that of others illustrates the power of eQTL analysis for gene discovery (25,47,48).…”
Section: Discussionmentioning
confidence: 81%
“…An eQTL study is based on treating expression as a quantitative trait and associating it with genetic variation. eQTL studies have been tremendously successful, and have identified many loci involved in gene regulation (Ghazalpour et al 2008;Veyrieras et al 2008;Cookson et al 2009;Farber et al 2009;Hayes et al 2009;Jiménez-Gómez et al 2010;van Nas et al 2010;Steibel et al 2011;Gaffney et al 2012;Kabakchiev and Silverberg 2013;Francesconi and Lehner 2014). However, the traditional eQTL approach has some fundamental limitations.…”
mentioning
confidence: 99%
“…eQTL can be cis-or trans-acting, reflecting local and distant regulation of gene expression, respectively. They have been thoroughly studied in humans, yeast, plants, rats, mice, and worms (Brem et al 2002;Schadt et al 2003;Li et al 2006;Petretto et al 2006;Keurentjes et al 2007;Farber et al 2009). But, as far as we are aware of, all eQTL studies only focused on one time point or age group, whereas most complex traits and diseases such as cancer are age-related.…”
mentioning
confidence: 99%